Improving dimensional stability of injection molded wood plastic composites using cold and hot water extraction methods - Ozdemir, Ferhat; Ayrilmis, Nadir; Kaymakci, Alperen; Heon Kwon, Jin (Maderas. Ciencia y Tecnología, 2025)
Dimensional stability of wood plastic composites (WPCs) made from polypropylene and pine wood flour with and without coupling agent was investigated. The pine wood flour was prepared from wood chips which had been immersed, respectively, in boiling water for 1 h, 3 h, and 5 h or in distilled water for 1 day, 3 days, and 5 days at room temperature. It was found that thickness swelling (TS) and water absorption (WA) of the WPCs made using extracted wood were lower than those of WPCs produced with unextracted wood. The TS and WA values of WPCs decreased with extraction duration both for cold and hot water extraction. The effect of hot water extraction on the TS and WA properties of the WPCs was more pronounced than cold water extraction.